Kaolinization processes in the phyolitic rocks of Kefalos, Kos island, Aegean Sea, Greece - PAPOULIS, D.; TSOLIS - KATAGAS, P. (Bulletin of the Geological Society of Greece, 2001)
Kaolin occurrences in the South Kefalos peninsula, Kos island, Aegean sea, Greece, are products of hydrothermal alteration of rocks of rhyolitic composition. The chemical, mineralogical and textural characteristics of kaolin occurrences were investigated by X-Ray diffraction (XRD), Analytical scanning electron microscopy (SEM) and bulk rock chemical analyses. Attempts have been made to correlate the primary with secondary mineral assemblages and to establish the factors controlling the stepwise character of the transition from the fresh rhyolitic to kaolinized rocks. The kaolinization processes follows two main alteration pathways: I) Kfeldspar —» Mixed-layer kaolinite-smectite —» kaolinite —> dickite. II) Na-plagioclase —> kaolinite —> dickite